Pengaruh Teknik Relaksasi Otot Progesif Terhadap Penurunan Tingkat Kecemasan Pasien Covid-19 Di Kota Metro - Resa Livia Nica; Amalia; Tubagus Erwin Nurdiansyah; Ahmad Khaironi (STIKes IMC Bintaro, 2023)
Cases of Covid-19 in the world is 100,801,465 (100 million) cases. This disease outbreak causes anxiety, fear and anxiety to everyone. Based on the results of research in Hubei, China, 62 (0.9) experienced severe anxiety, 196 (2.7%), moderate anxiety and 1518 (21.3%) mild anxiety, one way to reduce anxiety is to perform progressive muscle relaxation. Reducing the Anxiety Level of Covid Patients at Iringmulyo Public Health Center, Metro City in 2021. Quantitative research, quasi-experimental design or quasi-experimental two group pretest-posttest approach, Location at Iringmulyo Public Health Center, Metro City in june - july 2021. The population of Covid patients is 63. The sample size in the experimental study was 30 respondents divided into 2 groups, namely control and intervention groups. Collecting data using a questionnaire. univariate, bivariate analysis. Thc rcsults of thc study found that thc avcragc anxicty of Covid-19 paticnts bcforc bcing givcn progrcssivc musclc rclaxation tcchniqucs was 54.2, aftcr it was 27.0. It is known that thc avcragc anxicty of Covid-19 paticnts bcforc in thc control group was 51.6, aftcr was 35.8. Thcrc is an cffcct of Progrcssivc Musclc Rclaxation Tcchniqucs on Rcducing Anxicty Lcvcls of Covid Paticnts at Iringmulyo Public Hcalth Ccntcr, Mctro City in 2021 (p valuc = 0.000). It is hopcd that hcalth workcrs will makc SOPs rclatcd to progrcssivc muscle relaxation therapy to control anxiety.